THE THEME OF THE ENDLESS COLUMN IN THE WORKS OF CONSTANTIN BRÂNCUŞI AND TIBERIU OLÁH - FEKETE, Adél (Studia Universitatis Babes-Bolyai Musica, 2009)
This short study aims to present similarities, common features between two works of art. Although they come from different artistic domains, both were parented by Romanian artists, but their commonly shared characteristics just begin to unfold this point. Other aspects of their relationship are presented here, coming from many different points of view like common ars poetica and aesthetics, based on the principle of simplicity; similarities in construction and structure; the use of the principles of repetition, variation and antithesis.